Fabrication and machining performance of powder compacted alumina based cutting tool - Abu Bakar, Hadzley; Fahmi, Naim; Mokhtar, Faiz; Tamin, Norfauzi; Azlan, Umar; Adam, Abdul Aziz; Izamshah, Raja; Kasim, Shahir (2018)
This study focuses on the fabrication of alumina based cutting tool for machining application. Specific weight of alumina powders were pressed in a mold using hydraulic press at 8 tons before compressed through Cold Isostatic Press (CIP) at 30000 psi. Green body then was dried and sintered at 1700 °C at 4 hours sintering time to form solid cutting tools. These cutting tools were then tested in turning operation to machine AISI 1045 with different cutting speeds. The results shows that CIP pressed alumina cutting tool obtained the hardness of 83.2 HRA which is considered adequate to machine AISI 1045 steel. The shrinkage of alumina powders recorded about 7% form green compact to sintered body. In terms of flank wear, the alumina cutting tool demonstrated decreased wear rate as the cutting speed increased from 150 m/min to 225 m/min. Wear area focused at the edge of cutting tool due to small nose radius with the minimum wear rate recorded at 0.0025 mm/s for 225 m/min cutting speed. The newly fabricated cutting tools can be improved if finer or secondary reinforced particles were used.